76.3k views
1 vote
Solve the equation (linear equation)


8^(2x+7) = ((1)/(32))^(3x)

User Insoo
by
5.0k points

1 Answer

5 votes

Answer:
x=-1

Explanation:

By the negative exponent rule, you have that:


((1)/(a))^n=a^(-n)

By the exponents properties, you know that:


(m^n)^l=m^((nl))

Therefore, you can rewrite the left side of the equation has following:


((1)/(8))^(-(2x+7))=((1)/(32))^(3x)

Descompose 32 and 8 into its prime factors:


32=2*2*2*2*2=2^5\\8=2*2*2=2^3

Rewrite:


((1)/(2^3))^(-(2x+7))=((1)/(2^5))^(3x)

Then:


((1)/(2))^(-3(2x+7))=((1)/(2))^(5(3x))

As the base are equal, then:


-3(2x+7)=5(3x)

Solve for x:


-6x-21=15x\\-21=15x+6x\\-21=21x\\x=-1

User Kelle
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.